Taxonomical study of Halothamnus iraqensis Botsch. (Amaranthaceae) in Al-Tar Caves, Karbala, Iraq (Journal of Pharmaceutical Negative Results, 2022)
Halothamnus iraqensis Botsch. (Amaranthaceae) It is one of the endemic plant species in Iraq, which studied taxonomically from the morphological and anatomical aspect of the plant stem, as well as studying the shapes of stem cells, leaves and the stomata complex, also geographical with habitat and ecological study to give a clearer picture of this plant and to facilitate the diagnosis process for other researchers. The results that showed that this species is a small shrub to 50 cm tall, has stiff woody stem and succulen which branching very copiously from base. Contains Unicellular hairs and Multicellular hairs, The average length of the epidermal cells on surfaces of the leaf was about 55.55 m and 43.25 m on adaxial and abaxial surfaces, respectively. Adaxially, width of the epidermal cells was about 38.56m while abaxially, it was about 31.22 m.